PEMASARAN KOPI PADA ERA KE TIGA DI KABUPATEN KUNINGAN - Wachdijono Wachdijono; Akhmad Jaeroni (Universitas Galuh Ciamis, 2021)
Coffee marketing in the third era was marked by symptoms that led to the synergy of the subsystems in the coffee agribusiness. This study aims to describe the indicators of coffee marketing in the third era in Kuningan Regency. This research uses descriptive method. The population consists of four elements, namely: coffee farmers, coffee processors, coffee presenters and coffee consumers. The sample size was determined intentionally, namely: 60 coffee farmers, 30 coffee processors, 15 coffee presenters and 50 coffee consumers. Research time during August–November 2020. The results of the study conclude that the marketing of coffee in the third era in Kuningan Regency has not been synergized among the subsystems so that the indicators have not been fulfilled optimally, which results in the benefits/profit opportunities that exist in coffee agribusiness that have not been obtained proportionally. For this reason, a stronger synergy is needed between the agribusiness subsystems initiated by the local Plantation Service.